background image

From this

x

 T

FCD

(

A

;

B

)

R

y

⇔ ∀

f

R

:

x

[

f

]

y

.

1. From the former

y

atoms

B

 T

FCD

(

A

;

B

)

R

x

y

B

 T

FCD

(

A

;

B

)

R

x

0

B

⇔ ∀

f

R

:

y

B

h

f

i

x

0

B

y

T

h

atoms

B

i{h

f

i

x

|

f

R

} ⇔

y

atoms

B

T

B

{h

f

i

x

|

f

R

}

for every

y

atoms

B

.

B

is atomically separable by the corollary 17 in [3]. Thus

 \

FCD

(

A

;

B

)

R

x

=

\

B

{h

f

i

x

|

f

R

}

.

Theorem 57.

Let

A

,

B

,

C

are posets of filter objects over some boolean lattices,

f

FCD

(

A

;

B

)

,

g

FCD

(

B

;

C

)

,

h

FCD

(

A

;

C

)

. Then

g

f

h

g

h

f

1

.

Proof.

g

f

h

a

atoms

1

A

, c

atoms

1

C

:

a

[(

g

f

)

h

]

c

a

atoms

1

A

, c

atoms

1

C

: (

a

[

g

f

]

c

a

[

h

]

c

)

a

atoms

1

A

, b

atoms

1

B

, c

atoms

1

C

: (

a

[

f

]

b

b

[

g

]

c

a

[

h

]

c

)

b

atoms

1

B

, c

atoms

1

C

: (

b

[

g

]

c

b

[

h

f

1

]

c

)

b

atoms

1

B

, c

atoms

1

C

:

b

[

g

(

h

f

1

)]

c

g

h

f

1

.

3.9 Direct product of elements

Definition 58.

Let

A

and

B

are posets with least elements and

A ∈

A

,

B ∈

B

.

Funcoidal product

of

A

,

B ∈

A

is such a pointfree funcoid

A ×

FCD

B ∈

FCD

(

A

;

B

)

that

X

[

A ×

FCD

B

]

Y ⇔ X

A

A ∧ Y

B

B

.

Proposition 59.

A ×

FCD

B

is really a pointfree funcoid and for every

X ∈

A

hA ×

FCD

B iX

=

(

B

if

X

A

A

;

0

B

if

X ≍

A

A

.

Proof.

Obvious.

Proposition 60.

Let

A

and

B

are bounded posets,

f

FCD

(

A

;

B

)

,

A ∈

A

,

B ∈

B

. Then

f

⊆ A ×

FCD

B ⇔

dom

f

⊆ A ∧

im

f

⊆ B

.

Proof.

If

f

⊆ A ×

FCD

B

then dom

f

dom

(

A ×

FCD

B

)

⊆ A

, im

f

im

(

A ×

FCD

B

)

⊆ B

. If

dom

f

⊆ A ∧

im

f

⊆ B

then

∀X ∈

A

,

Y ∈

B

: (

X

[

f

]

Y ⇒ X

A

A ∧ Y

B

B

);

consequently

f

⊆ A ×

FCD

B

.

Theorem 61.

Let

A

,

B

are sets of filters over boolean lattices. For every

f

FCD

(

A

;

B

)

and

A ∈

A

,

B ∈

B

f

FCD

(

A

;

B

)

(

A ×

FCD

B

) =

I

B

FCD

(

B

)

f

I

A

FCD

(

A

)

.

Proof.

From above

FCD

(

A

;

B

)

is a (complete) lattice.

12

Section 3